2021
DOI: 10.1109/access.2021.3113813
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Four Different Ways of Calculating Yield Index SSSpk Based on Information of Control Chart, and Six Sigma, to Measuring the Process Performance in Industries: Case Study in Aden’s Oil Refinery, Yemen

Abstract: Process capability index PCIs have long been used to assess process efficiency in the manufacturing. While PCIs assess the process stability and efficiency, real measurements of product quality depended on estimate the standard deviation for a short-term variance was calculated as the base approach in several previous studies for measuring PCIs. Studies in recent years seek to estimate shift of the process mean from target. In today's smart manufacturing production climate, manufacturers keep track of producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It is obvious that accuracy index δ and precision index γ are two important parameters of the process capability index, as well as two important indices for evaluating the process quality level. For example, when |δ| ≤ 1.5/k and γ ≤ 1/k, then the process quality reaches the k-sigma quality level [20]. Raising the process precision and process accuracy can increase the values of process capability indices as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious that accuracy index δ and precision index γ are two important parameters of the process capability index, as well as two important indices for evaluating the process quality level. For example, when |δ| ≤ 1.5/k and γ ≤ 1/k, then the process quality reaches the k-sigma quality level [20]. Raising the process precision and process accuracy can increase the values of process capability indices as well.…”
Section: Discussionmentioning
confidence: 99%
“…As the process was statistically controlled, this study used the statistical testing method as well as applied the control chart data in statistical process control, in order to propose a model to evaluate process precision and accuracy. Plenty of studies have suggested that as the process quality attains the k-sigma quality level, the required conditions are (1) |δ| ≤ 1.5/k and (2) γ ≤ 1/k [20]. That is, when the accuracy index is bigger than 1.5/k (δ > 1.5/k), it is learned that the process is excessively shifted to the right of tolerance, so the process must be improved.…”
Section: Evaluation Of Process Precision and Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to use 4.5 sigma to estimate the upper and lower control limits of the oil refining process in this study because 3 sigma estimation is inadequate. Despite the fact that there are a number of estimation approaches, studies have shown that 4.5 sigma is efficient at reducing variance and thus improving process efficiency (Chakraborti et al 2008;Schoonhoven et al 2009 ;Ravichandran 2016;Ali, Ghaffar, Al-Swidi, & Ahmad, 2021;and Almazah, Ali, Eltayeb, & Atta, 2021). Control limits can be determined using the following mathematical expression, given k as the sample size of n and 4 items with means the (d) is set according to this equation; as the constant (𝑘)…”
Section: Six Sigma Withmentioning
confidence: 99%
“…Not only can this process capability analysis chart measure the process quality, but it also can analyze whether the process defect is caused by excessive process variation or process deviation, providing engineers with suggestions and directions for process improvement [11,12]. Therefore, many studies have applied the process capability index to the process capability analysis chart as one of the tools which promote the improvement process of the six-sigma DMAIC method [13][14][15].…”
Section: Introductionmentioning
confidence: 99%